On state of understanding for bioresources of Antarctic, their status and commercial using - Andrey F. Petrov (Известия ТИНРО, 2016)
Modern state of biological resources in Antarctic is considered using comprehensive systemic analysis of historical and present data of Russian and international fisheries researches, catch data, scientific observations made by Russia and other CCAMLR countries, and materials from CCAMLR database. Distribution and abundance of krill and toothfish is presented for the main fishing grounds in 2013-2014. Legal treatment is given for current and projected state of the bioresources accessible for Russian fishery. Scientific recommendations for rational exploitation of the resources by Russian fishing fleet are presented for the season of 2014/15 and further.